2004
DOI: 10.1016/j.febslet.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of smooth muscle contractility by CHASM, a novel member of the smoothelin family of proteins

Abstract: Cyclic nucleotides acting through their associated protein kinases, the cGMP-and cAMP-dependent protein kinases, can relax smooth muscles without a change in free intracellular calcium concentration ([Ca 2þ ] i ), a phenomenon referred to as Ca 2þ desensitization. The molecular mechanisms by which these kinases bring about Ca 2þ desensitization are unknown and an understanding of this phenomenon may lead to better therapies for treating diseases involving defects in the contractile response of smooth muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 44 publications
1
64
0
Order By: Relevance
“…The finding that SMTNL1 activity and intracellular localization are regulated by Ser-301 phosphorylation offers a mechanism to explain this paradox. In previous work we had shown that agonists that elevate intracellular cAMP or cGMP promote phosphorylation of Ser-301 in vivo, and phosphorylation of this amino acid inhibits the ability of SMTNL1 to inhibit PP1M in vitro (27,28). Herein we now show that phosphorylation Ser-301 also promotes translocation of SMTNL1 to the nucleus.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The finding that SMTNL1 activity and intracellular localization are regulated by Ser-301 phosphorylation offers a mechanism to explain this paradox. In previous work we had shown that agonists that elevate intracellular cAMP or cGMP promote phosphorylation of Ser-301 in vivo, and phosphorylation of this amino acid inhibits the ability of SMTNL1 to inhibit PP1M in vitro (27,28). Herein we now show that phosphorylation Ser-301 also promotes translocation of SMTNL1 to the nucleus.…”
Section: Discussionsupporting
confidence: 55%
“…Ser-301 Phosphorylation Regulates Translocation of SMTNL1 to the Nucleus-SMNTL1 is phosphorylated at Ser-301 in vivo in response to agonists that elevate intracellular cGMP or cAMP (27,28). Our finding that SMTNL1 deletion induces expression of MYPT1 in both smooth and striated muscle tissues, and that this effect is greatly exaggerated during pregnancy, suggests a direct role for SMTNL1 in the regulation of MYPT1 expression.…”
Section: Pregnancy Regulates the Expression Of Mypt1 In Striated And mentioning
confidence: 76%
See 1 more Smart Citation
“…Both myosin light chain kinase and myosin phosphatase are regulated by several accessory proteins, and one such protein is smoothelin-like protein 1 (SMTNL1) (9). Mouse SMTNL1 is divided into two separate domains: a unique N-terminal domain (amino acids 1-346) and a C-terminal single, type-2 calponin homology domain (amino acids 346 -459) that is helix-rich and globular in structure essential for binding tropomysin (9,10). Physiological studies in smtnl1 Ϫ/Ϫ mice indicate that the protein plays a key role in modulating the contractile activity of smooth and striated muscle and is involved in adaptation in response to exercise and pregnancy (11,12).…”
Section: Smtnl1 Is a Bifunctional Co-regulator Of Pr-b Signaling And mentioning
confidence: 99%
“…Immunoprecipitation, Immunoblotting, and Mass Spectrometry-Uterus samples of WT and smtnl1 Ϫ/Ϫ mice in day 0 and 14 of pregnancy were homogenized as described previously (9). Samples were processed for immunoprecipitation (IP) and immunoblotting with specific antibodies against SMTNL1, PR, and ER␣.…”
Section: Mouse Colony Maintenance and Pregnancy Studies-the Smtnl1mentioning
confidence: 99%